TORTOR BATAK TOBA DALAM KONTEKS PARIWISATA DI MUSEUM HUTA BOLON SIMANINDO KABUPATEN SAMOSIR - F. Kristina Siallagan; Yusnizar Heniwaty (Universitas Negeri Medan, 2018)
Abstract − This Research purposed to figure out the Performance of tortor Batak Toba as one of tourism package of Museum Huta Bolon Simanindo and its impact of increasing tourism visit tothe Museum. The method in this research uses descriptive qualitative method. The population are; the Department of Culture and Tourism Samosir, Museum Huta Bolon Simanindo officers, musicians, dancers, Public figures/Leader, community of Simanindo, and the tourists. The sample was part of the study population. The place of this research was taken in the Museum Huta Bolon Simanindo -Samosir regency. The data collection was done by observation, interviews, documentation and literature study. Generally, it discusses the development of cultural tourism through the performances of tortor Batak Toba which is the potential resources of local communities as cultural attractions. Cultural attractions are expected to have contributed to the preservation of culture in local communities. Tortor performance is held on an open stage in the old village of Huta Bolon. Performanceis no longer sacred but still follow the traditional rules of adatni gondang, such as the number of gondang types, rules of how to ask certain gondang types, the rules of motion in tortor, apparel and equipment. Another packaging of forms of performance that is of short duration and dense, full of variety, imitation of the original forms, and effective cost. Travelers can enjoy the Batak Toba culture, such as music, dance, historical objects, and the feel of Batak Toba villages. Overall the show is divided into two sessions, the first are Tortor Lae-lae, Tortor Mula-mula, Tortor Mula Jadi, Tortor Mangaliat, Tortor Marsiolop-olopan, tortor tortor Si Boru Si Doli, and Tortor Pangurason. Performing the second session has been packed in line with its objectives, namely manortor together, Tortor Tunggal Panaluan, and Tortor Si Gale-gale. Keywords: Tortor Batak Toba, Context Tourism